1995
DOI: 10.1210/mend.9.4.7659091
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor steroidogenic factor 1 is essential for the formation of the ventromedial hypothalamic nucleus.

Abstract: The nuclear receptor steroidogenic factor 1 (SF-1) regulates the biosynthesis of the two essential mediators of male sexual differentiation, androgens and Müllerian-inhibiting substance, and is required for adrenal and gonadal development and gonadotropin expression. SF-1 is also expressed in the embryonic ventral diencephalon, subsequently localizing to the ventromedial hypothalamic nucleus, a region important for reproductive behavior. Mice lacking SF-1 secondary to targeted disruption of the Ftz-F1 gene had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
138
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(145 citation statements)
references
References 15 publications
5
138
0
2
Order By: Relevance
“…Later studies showed that SF-1 is also present in the pituitary and ventromedial nucleus of the hypothalamus (20 -22). Consistent with its expression pattern, SF-1 knock-out mice lack adrenal glands and gonads, exhibit ventromedial nucleus of the hypothalamus and pituitary gonadotrope abnormalities, and display female internal genitalia (21,(23)(24)(25). In humans, the role of SF-1 in male sex differentiation is supported by the identification of SF-1 gene mutations in some 46,XY sex-reversed patients: a dominant de novo heterozygous G35E mutation (26), a recessive homozygous R92Q mutation (27), and a heterozygous deletion of eight nucleotides causing a frameshift mutation and C-terminal truncation of the SF-1 protein (28).…”
mentioning
confidence: 59%
“…Later studies showed that SF-1 is also present in the pituitary and ventromedial nucleus of the hypothalamus (20 -22). Consistent with its expression pattern, SF-1 knock-out mice lack adrenal glands and gonads, exhibit ventromedial nucleus of the hypothalamus and pituitary gonadotrope abnormalities, and display female internal genitalia (21,(23)(24)(25). In humans, the role of SF-1 in male sex differentiation is supported by the identification of SF-1 gene mutations in some 46,XY sex-reversed patients: a dominant de novo heterozygous G35E mutation (26), a recessive homozygous R92Q mutation (27), and a heterozygous deletion of eight nucleotides causing a frameshift mutation and C-terminal truncation of the SF-1 protein (28).…”
mentioning
confidence: 59%
“…GST fusion proteins were incubated with an equal amount of immunoprecipitated GCN5 in the presence of 2 l of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetyl-CoA (59 mCi/mmol, Amersham Pharmacia Biotech) for 2 h at 37°C. Proteins were solubilized with SDS-PAGE sample buffer and resolved on 10% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…The SF-1 binding site in the Mullerian-inhibiting substance promoter, a key hormone involved in male sex differentiation, is required for the maintenance of Mullerian-inhibiting substance expression (10). Disruption of the SF-1 gene in mice leads to the complete agenesis of the adrenals and gonads and to abnormalities in the ventromedial hypothalamus (11,12). A mutation in the human gene encoding for SF-1 (FTZF1; fushi tarazu-related factor 1) has been described in a phenotypically female patient exhibiting primary adrenal failure and XY sex reversal (13).…”
mentioning
confidence: 99%
“…The functions of the orphans are less well understood, although it is thought that they have crucial roles in a variety of processes. Thus, the profound effects of the knock out of the SF-1/FTZ-F1 (8,9) or HNF-4 (10) genes demonstrate that both have essential developmental functions. The remarkable conservation of the Coup-TFs and other orphans in mammalian and non-mammalian species (11) provides a somewhat less direct, but compelling argument for an important role.…”
mentioning
confidence: 99%